2018
DOI: 10.1007/s13201-018-0727-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of crude oil-contaminated water with chemically modified natural fiber

Abstract: The dependence of Nigerian Government on foreign technology for oil spill cleanup in its water bodies does not add local content value in the development of the Nation's economy. Acetylation of natural cellulose gives a material with high sorption capacity for oil in water. This research investigates crude oil sorption from water using acetylated and unacetylated lignocellulose. Oil palm empty fruit bunch (OPEFB) and cocoa pod (CP) were acetylated under mild conditions. The acetylated (modified) and unacetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…5, which reveals that the removal efficiency decreased with increasing particle size, which is because more smaller particle and more specific area provided for solution and also less mass resistance provided to surrounding stream [3]. This finding was with agreement with finding of [7] and [35]. So particle size in the range of 150-300 micron was adopted in this study.…”
Section: Effect Of Particle Sizesupporting
confidence: 81%
“…5, which reveals that the removal efficiency decreased with increasing particle size, which is because more smaller particle and more specific area provided for solution and also less mass resistance provided to surrounding stream [3]. This finding was with agreement with finding of [7] and [35]. So particle size in the range of 150-300 micron was adopted in this study.…”
Section: Effect Of Particle Sizesupporting
confidence: 81%
“…Figures 1, 2 and 3 represents the IR spectra of unacetylated and acetylated OPEFB, POBP and CP respectively. The FTIR spectra showed that after acetylation, ester bands were shifted and enhanced at around 1745 cm −1 (carbonyl C=O stretching of ester), 1375 cm −1 (C–H in –O(C=O)–CH 3 ), 1240 cm −1 (C–O stretching of acetyl group) and 1020 cm −1 (C–O stretching vibrations in cellulose) [1, 14, 15, 17]. Thus, confirming the successful acetylation of the lignocellulosic samples.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation is a technique for increasing the sorption efficiency of the sorbent and can be facilitated by the use of a catalyst ( N -bromosuccinimide, N -methylpyrrolidone, 4-dimethylaminopyridine) or not. In acetylation, the hydroxyl groups in the cellulose structure are converted to oleophilic acetate groups (O-CO-CH 3 ) through reaction with acetic anhydride, lowering the hydrophilic properties of the sorbent and enhancing the oleophilic ones [ 46 , 50 , 76 , 77 , 78 ]. As a result of this modification, the oil uptake is drastically increased, while the water sorption is respectively reduced.…”
Section: Modification Methods For Hydrophobicity Improvementmentioning
confidence: 99%
“…As a result of this modification, the oil uptake is drastically increased, while the water sorption is respectively reduced. Acetylated sorbents have bulkier forms because of the difference in molecular weight between OH and O-CO-CH 3 , which is referred to as weight percent gain [ 46 , 78 ].…”
Section: Modification Methods For Hydrophobicity Improvementmentioning
confidence: 99%
See 1 more Smart Citation